Improving endoscopic resolution and sampling: fluorescence techniques. (1st June 2003) - Ell, C
Abstract : Gastrointestinal tumours are usually associated with a poor prognosis, as most are only diagnosed at an advanced stage. Every effort to improve intraluminal diagnosis in gastroenterology must therefore be aimed at diagnosing gastrointestinal tract tumours at the earliest stage possible.